2009
DOI: 10.1105/tpc.109.072124
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type–Specific Chromatin Decondensation of a Metabolic Gene Cluster in Oats    

Abstract: Transcription-related chromatin decondensation has been studied in mammals for clusters of structurally and/or functionally related genes that are coordinately regulated (e.g., the homeobox locus in mice and the major histocompatability complex locus in humans). Plant genes have generally been considered to be randomly distributed throughout the genome, although several examples of metabolic gene clusters for synthesis of plant defense compounds have recently been discovered. Clustering provides for genetic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 43 publications
4
53
0
Order By: Relevance
“…Clustering also may enable co-ordinate regulation of gene expression at the level of chromatin (3,6,8,9,14,21). Consistent with this notion, we recently showed that expression of the avenacin gene cluster in oat is associated with cell typespecific chromatin decondensation (40). The genes within the marneral and thalianol clusters are coordinately expressed, and both clusters have very similar root-specific expression patterns (Fig.…”
supporting
confidence: 65%
“…Clustering also may enable co-ordinate regulation of gene expression at the level of chromatin (3,6,8,9,14,21). Consistent with this notion, we recently showed that expression of the avenacin gene cluster in oat is associated with cell typespecific chromatin decondensation (40). The genes within the marneral and thalianol clusters are coordinately expressed, and both clusters have very similar root-specific expression patterns (Fig.…”
supporting
confidence: 65%
“…Phylogenetic analysis shows that MT1 lies within a clade of methyltransferases that consists mainly of O-methyltransferase enzymes with roles in secondary metabolism ( Figure 2B; see Supplemental Data Set 1 online), although two characterized members of this clade (Limonium latifolium b-alanine-N-methyltransferase and Ruta graveolens anthranilate-N-methyltransferase) are known to have N-methyltransferase activity (Liscombe and Facchini, 2007;Rohde et al, 2008), consistent with a possible role for MT1 as an N-methyltransferase. Avenacins are synthesized in the epidermal cells of the root tip, and the expression of genes that encode the previously characterized steps in the biosynthetic pathway is restricted to these cells (Qi et al, 2006;Wegel et al, 2009;Mugford et al, 2009). Quantitative PCR analysis revealed that the MT1 transcript is most abundant in whole root and root tip samples, low in the upper root, and not detectable in young leaves ( Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…This is similar in the case of other mutants blocked in this pathway, with the exception of the sad3 and sad4 mutants, which accumulate a toxic form of avenacin that is incompletely glucosylated and that disrupts root development (Mylona et al, 2008). While containment of toxic intermediates may contribute to the selection driving the evolution of plant natural product gene clusters, it seems likely that other factors, such as coinheritance of beneficial combinations of alleles of the different pathway genes and coordinated regulation at the level of chromatin, are also likely to be important (Wegel et al, 2009;Chu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that other genes of the ABDS gene cluster are involved in these modifications, such as hydroxylation, acylation, and/or glycosylation, although these genes are not as tightly coexpressed with CYP705A1 and ABDS, which is also the case in the thalianol cluster. The forces driving the evolution of gene cluster assembly in terpene metabolism are not fully understood; however, it has been suggested that gene clustering facilitates the regulation of multiple genes at the level of chromatin and prevents the accumulation of possible cytotoxic products (Field and Osbourn, 2008;Wegel et al, 2009;Field et al, 2011). In summary, the formation of DMNT in Arabidopsis roots evolved as part of a triterpene biosynthesis gene cluster indicating plasticity in the biosynthesis of homoterpene volatiles.…”
Section: Evolution Of Dmnt Biosynthesis In Arabidopsis Via Triterpenementioning
confidence: 99%